FORMULATION OF PEEL-OFF GEL MASK OF COCOA SKIN EXTRACT (Theobroma cacao L) WITH VARIED CONCENTRATION GELLING AGENT - Yunita Dian Permata Sari; Diyan Sakti Purwanto; Umi Nafisah (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Cocoa shells are waste from the plantation industry, with a fairly good potential source of energy and protein. The ethanol extract of cocoa shells contains alkaloids, flavonoids, phenols, and tannins. Cocoa shell extract has strong antioxidant activity with an IC50 value of 17.21 ppm and has sunscreen activity. This study aimed to determine the formulation and physical test of a peel-off gel mask with cocoa shell extract (Theobroma cacao L) and to determine its effect. The research method used was an experimental method with variations in the concentration of a combination of HPMC and PVA of 2%:10%, 3%:9%, 4%:8%, 5%:7%, and 0%:12%. The physical tests used on the peel-off gel mask with cocoa shell extract (Theobroma cacao L) included organoleptic, homogeneity, pH, spreadability, drying time, adhesiveness, viscosity, and cycling tests. Based on the results of the research carried out, peel-off gel mask has the characteristics of a brown color, a distinctive extract smell and a thick texture, homogeneous for F1 and F5, and not homogeneous for F2, F3, and F4, sticking force 4.53±0.24 seconds; 5.45±0.36 seconds; 8.94±0.64 seconds; 11.23±0.72 seconds; 3.87±0.70 seconds; spreadability 3.99 ± 0.18 cm; 3.33±0.31 cm; 3.47±0.78 cm; 3.32±0.50 cm; 3.05±0.42 cm; pH 6.17 ± 0.10; 6.16±0.03; 6.15±0.10; 6.11±0.05; 6.42±0.03; viscosity 19481.10±201.10; 20165.50±1.05; 20165.73±2.02; 20182.53±9.47; 14618.40±158.48. The physical stability of the gel mask preparations after treatment showed that the results of the peel-off gel mask preparations, F1 and F5, were stable. Keywords: peel-off gel mask, cocoa shell, extract, gelling agent